Odpowiedź :
Odpowiedź:
[tex]2\frac{1}{5} * 10 + 1 \frac{3}{4} = \frac{11}{5} * \frac{10}{1} + 1 \frac{3}{4} = \frac{11}{1} * \frac{2}{1} + 1 \frac{3}{4} = 22 + 1 \frac{3}{4} = 23 \frac{3}{4}\\[/tex]
[tex]3\frac{3}{4} + 2 \frac{2}{3} * 2 \frac{1}{4} = 3 \frac{3}{4} + \frac{8}{3} * \frac{9}{4} = 3 \frac{3}{4} + \frac{2}{1} * \frac{3}{1} = 3 \frac{3}{4} + 6 = 9 \frac{3}{4}[/tex]
[tex]2\frac{2}{5} * 1 \frac{2}{3} - 1 \frac{5}{6} = \frac{12}{5} * \frac{5}{3} - 1 \frac{5}{6} = \frac{4}{1} * \frac{1}{1} - 1 \frac{5}{6} = 4 - 1 \frac{5}{6} = 2 \frac{1}{6}[/tex]